2020
DOI: 10.1371/journal.pone.0232774
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of smoking cessation, alcohol reduction, diet and physical activity interventions in changing behaviours during pregnancy: A systematic review of systematic reviews

Abstract: BackgroundPregnancy is a teachable moment for behaviour change. Multiple guidelines target pregnant women for behavioural intervention. This systematic review of systematic reviews reports the effectiveness of interventions delivered during pregnancy on changing women's behaviour across multiple behavioural domains. MethodsFourteen databases were searched for systematic reviews published from 2008, reporting interventions delivered during pregnancy targeting smoking, alcohol, diet or physical activity as outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…By focusing on the health-related outcomes, we are missing essential behavioural information that has a direct impact on effectiveness. We discussed, in our previous paper [ 23 ], how important it is to measure behaviours to advance our understanding of the mechanisms within intervention research. If a behaviour-change intervention is not effective at reducing health-related risk, and the behaviour itself is not measured, then we are left questioning whether the behaviours are not relevant and we should cease trying to intervene to change that target behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…By focusing on the health-related outcomes, we are missing essential behavioural information that has a direct impact on effectiveness. We discussed, in our previous paper [ 23 ], how important it is to measure behaviours to advance our understanding of the mechanisms within intervention research. If a behaviour-change intervention is not effective at reducing health-related risk, and the behaviour itself is not measured, then we are left questioning whether the behaviours are not relevant and we should cease trying to intervene to change that target behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of effect could be due to the intervention failing to change the target behaviour (either at all or to the magnitude required to have a clinically important impact on health outcomes), in which case, are there alternative behaviour-change strategies which could be explored with a greater potential to impact health outcomes? We previously reported [ 23 ] that systematic reviews reported the effectiveness of interventions at changing maternal behaviours in 100% of the smoking and alcohol reviews identified, but for only 18% of diet and/or physical activity reviews. We see the opposite trend in this paper, where 66% of diet and/or physical activity systematic reviews reported a meta-analysis of health-related outcomes, compared with only 9% of the smoking reviews and no alcohol reviews.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA methylation that mediates between smoking and lower birth weight can also be a factor linking this unfavorable fetal outcome with adverse long-term health outcomes [35,36]. It should also be taken into account that smoking women may lead a different lifestyle that includes, for example, an unhealthy diet and other "unhealthy" behaviors [37].…”
Section: Discussionmentioning
confidence: 99%